2006
DOI: 10.2527/2006.8441030x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth-promoting agents and season on blood metabolites and body temperature in heifers1,2

Abstract: ABSTRACT:To assess the efficacy of growth-promoting agents among seasons, triiodothyronine (T 3 ), thyroxine (T 4 ), plasma urea nitrogen (PUN), IGF-I, and tympanic temperature (TT) were measured in summer and winter studies. Heifers (n = 9/pen) were allotted to 12 pens in both December and June. Pens were assigned to 1 of 6 growth promotant treatments: control (no growth promotant), estrogenic implant (E), trenbolone acetate implant (TBA), E + TBA (ET), melengestrol acetate (MGA), and ET + MGA (ETM). Blood sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 24 publications
2
18
0
1
Order By: Relevance
“…Considering the greater ADG and G:F observed in implanted heifers, one would expect that they utilized N better than control heifers. Supporting the present study, previous research indicated that heifers implanted with estradiol+trenbolone acetate had reduced plasma urea N compared to non-implanted controls or heifers implanted with either estradiol or trenbolone acetate alone (Mader & Kreikemeier, 2006). On the other hand, Cheatham (2005) indicated that SUN did not differ between implanted and non-implanted Holstein steers.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Considering the greater ADG and G:F observed in implanted heifers, one would expect that they utilized N better than control heifers. Supporting the present study, previous research indicated that heifers implanted with estradiol+trenbolone acetate had reduced plasma urea N compared to non-implanted controls or heifers implanted with either estradiol or trenbolone acetate alone (Mader & Kreikemeier, 2006). On the other hand, Cheatham (2005) indicated that SUN did not differ between implanted and non-implanted Holstein steers.…”
Section: Resultssupporting
confidence: 74%
“…This agrees with many previous reports indicating that implanting steers increases circulating IGF-1 (Lee & Henricks, 1990;Hunt et al, 1991;Cheatham, 2005). Furthermore, Mader & Kreikemeier (2006) found IGF-1 concentrations to be greater in estradiol+trenbolone acetate implanted heifers compared to controls, but found no differences in IGF-1 between controls and those animals implanted only with estradiol or trenbolone acetate. Moreover, serum IGF-1 is generally considered to be a GH dependent peptide (Florini et al, 1991).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies in controlled laboratory environments have made precise measurements of thermoregulatory effector response to heat stress but only over a period of several hours. Only recently have studies begun to make detailed measurements in the field over a period of time representative of normal exposure during the summer (Lefcourt and Adams 1996;BrownBrandl et al 2005a;Eigenberg et al 2005;Mader and Kreikemeier 2006;Gaughan et al 2008;Arias and Mader 2009). Current measurements include air (T a ) and black globe (T bg ) temperatures, temperature humidity index (THI), which combines T a and percent relative humidity (%RH), and the modified Black Globe Temperature Humidity Index (BGTHI), which utilizes T bg in place of T a .…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that estrogenic compounds increase plasma concentration of T 4 (Trenkle, 1997). Also, implants based in estrogenic substances and trembolone acetate appear to enhance the normal thyroid activity (Mader and Kreikemeier, 2006). In the present study, Synovex implants were used.…”
Section: Resultsmentioning
confidence: 99%